THE IMPACT OF TELEMEDICINE ON ACCESS TO PRIMARY CARE: CHALLENGES AND OPPORTUNITIES IN POST-PANDEMIC PRIMARY CARE - Carvalho Meneghetti, Matheus; Bromonschenkel De Angeli, Daiany; Musso Rabelo, Luna; Gomes Santos, Leonardo; Marcelo Pacheco Kokis, João; Silva Barbieri, Isabela; Costa dos Santos, Mariana; Barcelos Bicalho, Jhennyfer; Wagmacker Barbosa, Bárbara; Frasson Venturini, Lucas; Rebonato de Souza Ribeiro, Beatriz; Silva Pereira, Gabriela; et al. (Health and Society, 2024)
The COVID-19 pandemic has driven the implementation of telemedicine as a solution for maintaining access to healthcare, transforming the primary care landscape in many parts of the world. In Brazil, telemedicine has established itself as an essential tool for overcoming geographical and social barriers, facilitating access to basic care for populations that traditionally faced difficulties in accessing health services. This study seeks to investigate the impact of telemedicine on access to primary care, analyzing its main challenges and opportunities in the context of post-pandemic primary care. This study seeks to analyze the impact of telemedicine on access to primary care, exploring the main challenges and opportunities that arise with this modality of care. It also aims to identify practices and policies that can strengthen the implementation of telemedicine in Primary Care, ensuring that remote care is effective, safe and inclusive. This is a literature review, based on a qualitative approach, using the Scielo, Google Scholar and PubMed databases. To refine the research, the health descriptors “telemedicine”, “primary care”, “COVID-19”, and “equity in access to health” were selected, with a time frame between 2021 and 2023. Through a literature review, the study explores recent data on telemedicine in primary care, focusing on the main opportunities it offers, such as improved access and efficiency of services, as well as the challenges, including limited technological infrastructure in poor regions, privacy and confidentiality issues, and the need for adequate training for health professionals. Telemedicine enables more agile care and coverage of a larger population, but still faces obstacles related to digital accessibility and maintaining quality and continuity of care, especially for vulnerable groups. Telemedicine has therefore proved to be a strategic tool for expanding access to primary care, offering a viable alternative for reducing gaps in primary care. However, in order to maximize its impact, it is essential to overcome the technological challenges, guarantee information security and train health professionals in this new type of care. The continued use of telemedicine in the post-pandemic context presents an opportunity to strengthen the Unified Health System (SUS) in Brazil, expanding the reach of primary care and promoting greater equity in access to health.